2014
DOI: 10.1097/meg.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia from a patient perspective in inflammatory bowel disease

Abstract: IBD patients are mostly aware of the main signs and symptoms of anaemia. Oral iron is most commonly prescribed, but may cause dissatisfaction because of tolerability issues. Most patients prescribed intravenous iron are satisfied with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 14 publications
2
27
1
Order By: Relevance
“…According to GRADE, the quality of evidence (certainty of associations) in this review is moderate. This evidence, along with the treatment costs, patients’ values and preferences, 45 and other factors (clinical disease activity, severity of anemia, and previous intolerance to oral iron) should be considered to inform clinical decision making. Nevertheless, further high-quality (and adequately powered) randomized research, with clearly defined patient populations (eg, UC or CD, with mild, moderate, or severe anemia, etc.…”
Section: Discussionmentioning
confidence: 99%
“…According to GRADE, the quality of evidence (certainty of associations) in this review is moderate. This evidence, along with the treatment costs, patients’ values and preferences, 45 and other factors (clinical disease activity, severity of anemia, and previous intolerance to oral iron) should be considered to inform clinical decision making. Nevertheless, further high-quality (and adequately powered) randomized research, with clearly defined patient populations (eg, UC or CD, with mild, moderate, or severe anemia, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in recent years the topic has moved into the spotlight, because there is a growing body of evidence that anemia plays a key role in affecting IBD patients’ quality of life (QOL). In 2014, Danese et al analyzed anemia-related symptoms from an IBD patient’s perspective [15]. Symptoms widely reported by the 613 participants included fatigue, weakness, difficulties in concentrating, depressive mood, breathlessness, and sleeping difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Blumenstein et al revealed that in Germany 56.5% of IBD patients with anemia had not received adequate treatment [19]. Likewise, a web-based questionnaire of IBD patients showed that one third of those with anemia had not been treated accordingly [15]. Additionally, in a recent survey across 9 European countries, Stein et al revealed a high frequency of iron deficiency (ID) among IBD patients [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UC is associated with an architectural distortion of the intestinal epithelium and impaired mucosal barrier function (Chen et al, 2014;Zhang et al, 2017a). Patients with UC generally exhibit undesirable symptoms, such as fatigue, diarrhea, and rectal bleeding (blood in the stool) (Danese et al, 2014). Disease recurrences may affect the innermost layer of the large intestine and rectum, increasing the prevalence of colorectal cancer and the risk of extraintestinal diseases, such as iritis/uveitis, arthritis, major sclerosing cholangitis, and ankylosing spondylitis (Vavricka et al, 2015;Harbord et al, 2016).…”
Section: Introductionmentioning
confidence: 99%